(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
In this article, the purpose, tasks and main directions that determine the development of the economic activity of the railway transport-logistics system, the main problems that hinder the effective development of the railway transport-logistics system, directions for the development of the transport-logistics system and the theoretical basis for increasing the economic efficiency of the transport-logistics system are proposed